2017
DOI: 10.1021/acs.est.7b01087
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of p-Nitrophenol by Lignin and Cellulose Chars: H2O2-Mediated Reaction and Direct Reaction with the Char

Abstract: Chars and other black carbons are reactive toward certain compounds. Such reactivity has been attributed to reduction of O by persistent free radicals in the solid to HO, which then back-reacts with the solid to generate reactive oxygen species (ROS; especially HO). We studied the decomposition of p-nitrophenol (PNP) by pure lignin and cellulose chars aged in moist air or a vacuum at room temperature for up to a month. In air, the chars chemisorbed oxygen, a portion of which was liberated as HO when the char w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 38 publications
7
87
1
Order By: Relevance
“…Vigorous, rapid bubbling was observed upon the addition of H 2 O 2 to the biochar, consistent with observations of effervescence by Lawrinenko et al [21]. It is unclear whether the bubbling was due to reactions with the carbon structure of the material [28], or simply the decomposition of H 2 O 2 catalyzed by metal oxides in the biochar ash component [29], or a combination of the two mechanisms. A variety of reactions have been reported following the exposure of biochar to H 2 O 2 , depending on the biochar properties [30] and activation conditions (e.g., pH, presence of ferrous salts [31]).…”
Section: Biochar Activation Observationssupporting
confidence: 76%
“…Vigorous, rapid bubbling was observed upon the addition of H 2 O 2 to the biochar, consistent with observations of effervescence by Lawrinenko et al [21]. It is unclear whether the bubbling was due to reactions with the carbon structure of the material [28], or simply the decomposition of H 2 O 2 catalyzed by metal oxides in the biochar ash component [29], or a combination of the two mechanisms. A variety of reactions have been reported following the exposure of biochar to H 2 O 2 , depending on the biochar properties [30] and activation conditions (e.g., pH, presence of ferrous salts [31]).…”
Section: Biochar Activation Observationssupporting
confidence: 76%
“…155 When pCNPs are introduced into water these radicals can form H 2 O 2 and ROS, but most of these reactions typically take place within the first few hours after contact with water, as was recently observed for biomass-based chars where H 2 O 2 production peaked after approximately 1 hour and then declined. 156 CNP aggregation and pore blockage can decrease the release of free radicals and their products, similar to the reduced release of organic contaminants discussed in section 5.2. ROS deriving from pCNPs are capable of inducing the transformation of a range of organic contaminants including sulfadimidine, 157 1,3-dichloropropene, 158,159 p-nitrophenol, 160 trifluralin, 161 pendimethalin, 161 diethyl phthalate, 162 nitrobenzene, 163 and 2-chlorobiphenyl.…”
Section: Generation Of Reactive Oxygen Speciesmentioning
confidence: 57%
“…164 Some compounds can react directly with carbonaceous materials, as has been ob-served for chloropicrin 165 and p-nitrophenol. 156 Pignatello et al 116 suggested that the intrinsic reactivity of carbonaceous materials could be due to their redox behavior. The transformation of pCNPs is expected to have a strong effect on H 2 O 2 production, ROS release, and pCNP redox behavior.…”
Section: Generation Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…, but also can directly react with pollutants via nonradical pathways. In a biochar-mediated p-nitrophenol (PNP) decomposition, about 20% of PNP were degraded by •OH produced from the activation of H 2 O 2 by PFRs in biochar; while, about 80% of PNP were degraded via directly reacting with reactive sites, probably the hydroquinones in biochar through two one-electron transfers to produce reduced PNP (Yang et al 2017a). Also, another report attributed the degradation of PNP and p-aminophenol to the role of PFRs in biochar, where pollutants degrade mostly through direct contact with PFRs (Yang et al 2016a).…”
Section: •−mentioning
confidence: 99%